A educação de jovens e adultos na rede pública de Ensino no município de Tefé/Am: um estudo de caso sobre a participação das mulheres - Silva, Hilkmar Alves da (2023)
The main purpose of this dissertation is to analyze the social construction of Youth and Adult Education (YAE) in Tefé and the participation of women in this public policy. It is a quantitative research, of the case study type, with the participation of the municipal and state EJA education network in the municipality of Tefé, Amazonas. As collaborators we counted with the representation of coordinators, managers, teachers, and students who contributed to obtain data in the analyses about the current EJA scenario in the municipality of Tefé, through the application of questionnaires. For the case study, specifically, we counted on the collaboration of nine women students from Escola Estadual Corintho Borges Façanha, where we proposed to analyze the life trajectory and profile of these women students, through semi-structured interviews, based on two aspects. One aspect is related to the schooling trajectory from the beginning to the moment they interrupt their studies. The other covers the time from when they return to school, highlighting the reasons for dropping out, the challenges they faced, the changes they went through, the contributions of formal education in their lives, and their plans for post-conclusion. For this study, we guided the theoretical aspects based on the contributions of authors and documents (laws) about the theme. Among the authors and laws we cite: Arroyo (2006), Cardoso and Hage (2016), Haddad & Di Pierro (2000), Haddad & Siqueira (2015), Leite (2013), Freire (2006), Freire (2014) Federal Law No. 13.005/2014, Resolution No. 1/2021 CNE/CEB, Resolution 082/2021 CEE/AM. This study allowed us to understand the reality of Youth and Adult Education for the implementation of public policies aimed at this type of education in the context of the implementation of Youth and Adult Education in the municipality of Tefé. We tried to elucidate the challenges and possibilities for the construction of an education consistent with the reality of the Amazon region. We traveled this path looking at the school trajectories of women who faced the challenges of exclusion, lack of support, and machismo, and faced the challenge of returning to school in order to conquer spaces that are significant to them, such as financial independence and autonomy. These are trajectories of hope that make us reflect on the role of EJA within its specificities, based on the experiences and needs of the students in the Amazonian context.